Optimization of bamboo mesoparticle/nylon 6 composite mechanical properties using a response surface methodology - Salih, Abeer Adel; Zulkifli, Rozli; Azhari, Che Husna (Carl Hanser Verlag, 2024)
Fibers are widely used to reinforce polymer composites for various applications because of their mechanical properties and ease of manufacturing. Fiber reinforced polymers are being developed using synthetic fibers and natural fibers, including bamboo, bagasse, etc. The main goal of this work is to optimize the mechanical properties of bamboo mesoparticle/nylon 6 composites using a response surface methodology. The conditions used to achieve an optimal tensile strength, flexural strength, and impact strength were determined using a Box-Behnken design with three operational variables: alkali concentration, particle loading, and particle size. Based on the experimental design, experimental tests were conducted to develop a mathematical model and predict the mechanical properties of the bamboo mesoparticle/nylon 6 composites. The optimal conditions to produce a composite with a maximum tensile strength were achieved at an alkali concentration of 4 wt.%, a particle size of 1 lm, and a particle loading of 13.5 wt.%. The optimum conditions to produce a composite with a maximum flexural strength were achieved at an alkali concentration of 2 wt.%, a particle size of 1 lm, and a particle loading of 13.5 wt.%. Additionally, an alkali concentration of 4 wt.%, a particle size of 1 lm, and a particle loading of 9 wt.% produced a composite with the maximum impact strength. Overall, the results showed that the values predicted using the model correlated with the experimental values.